Weibel instability in relativistic quantum plasmas. (10th June 2015) - Mendonça, J T; Brodin, G
Abstract: Generation of quasi-static magnetic fields, due to the Weibel instability is studied in a relativistic quantum plasma. This instability is induced by a temperature anisotropy. The dispersion relation and growth rates for low frequency electromagnetic perturbations are derived using a wave-kinetic equation which describes the evolution of the electron Wigner quasi-distribution. The influence of parallel kinetic effects is discussed in detail.